Lessons learned from solar irrigation scaling in Asia and Africa - Bodach, Susanne; Al-Zu’bi, Maha; Tilahun, Seifu A. (International Water Management Institute, 2025)
Solar irrigation is emerging as a key pathway to expand reliable, low-emission water access for smallholder farmers in Asia and Africa. This report summarizes lessons on scaling solar irrigation from IWMI-led country teams and partners working in Nepal, Pakistan, India, Ghana, Nigeria, and East and Southern Africa. It draws on a structured “Solar Irrigation Scaling Challenge” process as a mechanism used to collect and synthesize country experiences and insights. Country cases document innovation bundles that link digital tools for groundwater and solar planning, inclusive business and financing models, and governance reforms supporting sustainable irrigation services. The analysis shows how blended finance, gender- and youth-responsive partnerships, and evidence-based policy and planning shape diverse scaling pathways in different policy and market contexts. It emphasizes that solar irrigation must be embedded in integrated water–energy–food strategies, with coordinated institutions, digital solutions, and equitable access mechanisms to prevent over-extraction and ensure long-term environmental and social sustainability.